Ischemic Stroke Risk Factor Profile at Prof. Dr. W. Z. Johannes Hospital, Kupang, East Nusa Tenggara - Pramanasari, Indra (AKSONA, 2024)
Highlight: Ischemic stroke is a major public health issue in Indonesia. Clinical data correlated to an ischemic stroke patient's prognosis. Several clinical factors and laboratory testing describe the tendency of ischemic stroke patients.   ABSTRACT Introduction: In Indonesia, ischemic stroke is a major public health issue. Clinical data correlates with an ischemic stroke patient's prognosis. Objective: This study aimed to provide an overview of clinical data in ischemic stroke patients from October 2020 to December 2021. Methods: This was a retrospective, descriptive study using medical records. A non-probability purposive sampling strategy with a total sampling method is used in this study. Age, gender, cardiac comorbidities, diabetes, repeated strokes, blood laboratory exams, electrolyte tests, alcohol consumption, and smoking habits were all observed variables. Results: The sample consisted of 242 ischemic stroke patients. The majority of patients (32.23%) were in the 61 to 70 age group, and men (57.4%) made up the majority of the sex group. Then, cardiac comorbidities were dominated by coronary artery disease (CAD), with 33 patients (57.4%) with 4 deaths (12.1%), while 15 patients (6.19%) were found with atrial fibrillation (AF), with 7 deaths (46.67%). Hypertension was found in 81.40% of patients, diabetes in 26.03% of patients, and recurrent stroke in 31.40% of patients. Active smokers make up 52.06% of all patients, and 18.18% are heavy alcohol drinkers. The majority of patients showed blood and electrolyte levels within the normal range, except for an increased leukocyte count and a decreased potassium level. Conclusion: The main risk factors obtained sequentially are hypertension, coronary artery diseases, active smokers, diabetes, and excessive alcohol consumption.